Pengaruh Kompetensi Individual, Motivasi Kerja Dan Kepuasan Karyawan Terhadap Kinerja Koperasi di Kecamatan Bandar Mataram Lampung Tengah - Aditia Armadan (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2019)
This research is motivated by the importance of improving the performance of cooperatives that can give a positive impact in achieving the objectives of the cooperative. Through performance measurement, cooperatives are encouraged to try to provide good value for organizational activities, business, and improve service cooperatives to its members and the community. When the competence of individual, work motivation, employee satisfaction is low then cooperative members, it’s can not provide maximum service and indirectly it will affect the performance of the cooperative. The purpose of this study was to determine the effect individual competence, work motivation, and employee satisfaction on the performance of cooperatives in Bandar Mataram District, Central Lampung.